Arsenic methylation and lung and bladder cancer in a case-control study in northern Chile - Melak, Dawit; Ferreccio, Catterina; Kalman, David; Parra, Roxana; Acevedo, Johanna; Pérez, Liliana; Cortés, Sandra; Smith, Allan H.; Yuan, Yan; Liaw, Jane; Steinmaus, Craig (Toxicology and applied pharmacology, 2014)
In humans, ingested inorganic arsenic is metabolized to monomethylarsenic (MMA) then to dimethylarsenic (DMA), although this process is not complete in most people. The trivalent form of MMA is highly toxic in vitro and previous studies have identified associations between the proportion of urinary arsenic as MMA (%MMA) and several arsenic-related diseases. To date, however, relatively little is known about its role in lung cancer, the most common cause of arsenic-related death, or about its impacts on people drinking water with lower arsenic concentrations (e.g., <200μg/L). In this study, urinary arsenic metabolites were measured in 94 lung and 117 bladder cancer cases and 347 population-based controls from areas in northern Chile with a wide range of drinking water arsenic concentrations. Lung cancer odds ratios adjusted for age, sex, and smoking by increasing tertiles of %MMA were 1.00, 1.91 (95% confidence interval (CI), 0.99–3.67), and 3.26 (1.76–6.04) (p-trend <0.001). Corresponding odds ratios for bladder cancer were 1.00, 1.81 (1.06–3.11), and 2.02 (1.15–3.54) (p-trend <0.001). In analyses confined to subjects only with arsenic water concentrations <200μg/L (median=60μg/L), lung and bladder cancer odds ratios for subjects in the upper tertile of %MMA compared to subjects in the lower two tertiles were 2.48 (1.08–5.68) and 2.37 (1.01–5.57), respectively. Overall, these findings provide evidence that inter-individual differences in arsenic metabolism may be an important risk factor for arsenic-related lung cancer, and may play a role in cancer risks among people exposed to relatively low arsenic water concentrations. •Urine arsenic metabolites were measured in cancer cases and controls from Chile.•Higher urine %MMA values were associated with increased lung and bladder cancer.•%MMA-cancer associations were seen at drinking water arsenic levels <200μg/L.